Oral infections and systemic diseases scientific evidence from an epidemiologic perspective - Lund Håheim, Lise (Cambridge Scholars Publishing, 2022)
Oral infections mainly affect oral health, but can also affect people's general health in several ways. This book gives an overview of the scientific evidence for linkages between oral infections and other systemic diseases. Much research has been carried out to find the most plausible reasons for associations and possible causal mechanisms in this regard. The last 20-30 years have opened up the field of the infection hypothesis in cardiovascular disease that was first introduced in the nineteenth century. The book also provides a short overview of oral infections and symptoms due to systemic.